2011
DOI: 10.1007/s11033-011-0728-z
|View full text |Cite
|
Sign up to set email alerts
|

Mineral trioxide aggregate promotes odontoblastic differentiation via mitogen-activated protein kinase pathway in human dental pulp stem cells

Abstract: Mitogen-activated protein kinase (MAPK) pathways are involved in stem cell differentiation. However, the odontoblastic differentiation-inducing effects by mineral trioxide aggregate (MTA) via MAPK pathways have not been clarified in human dental pulp stem cells (DPSCs). In this study we investigated the effects of MTA on cell viability and production of differentiation markers, and the involvement of MAPK signaling pathways in cultured human DPSCs. Cells were cultured with MTA, and the viability and differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
100
1
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 106 publications
(113 citation statements)
references
References 27 publications
8
100
1
4
Order By: Relevance
“…The roles of FGFR/MEK/Erk1/2 signaling in odontoblast differentiation and the crosstalk between the FGF/FGFR and BMP/BMPR signaling pathways in the stimulatory effects of FGF2 on odontoblast differentiation in our study are consistent with previously reported roles of these pathways in osteoblasts (Fakhry et al 2005;Spector et al 2005;Ye et al 2006;Yao et al 2011;Marie 2012;Marie et al 2012;Zhang et al 2012;Zhao et al 2012).…”
Section: Discussionsupporting
confidence: 93%
“…The roles of FGFR/MEK/Erk1/2 signaling in odontoblast differentiation and the crosstalk between the FGF/FGFR and BMP/BMPR signaling pathways in the stimulatory effects of FGF2 on odontoblast differentiation in our study are consistent with previously reported roles of these pathways in osteoblasts (Fakhry et al 2005;Spector et al 2005;Ye et al 2006;Yao et al 2011;Marie 2012;Marie et al 2012;Zhang et al 2012;Zhao et al 2012).…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, TNF-α treatment activates the p38 pathway in dental pulp cells via phosphorylation of p38 and inhibition of p38 diminishes the expression of DPP and DSP38. MTA can induce odontoblastic differentiation of human DPSCs via activation of MAPK signaling42. In a previous study, we demonstrated that LPS can promote the odontoblastic differentiation of human DPSCs via MAPK signaling pathway19.…”
Section: Discussionmentioning
confidence: 85%
“…MAPK pathway, which is a non-classical pathway, plays a crucial role in cell growth, proliferation, differentiation and apoptosis. It mainly consists of three parallel mechanisms, i.e., extracellular signal regulated kinases (ERKs), c-Jun N-terminal kinases (JNKs) and p38 MAPK43. The three parallel pathways play crucial roles in regulating the odonto/osteogenic differentiation of many cell types, such as DPSCs, PDLSCs, SCAPs and MSCs893844.…”
Section: Discussionmentioning
confidence: 99%